Math and science for young children - Charlesworth, Rosalind; Lind, Karen (Belmont, Calif. : Wadsworth Pub Co., 2013)
Math and science for young children is a unique reference that focuses on the integration of math and science in early childhood education programs, while addressing other important areas of child development during the crucial birth-through-eight age range. It also carefully addresses the ever-changing and significant national standards of the following organizations: The National Association for the Education of Young Children (NAEYC), National Council of Teachers of Math (NCTM), National Science Teachers Association (NSTA), American Association for the Advancement of Science (AAAS), and the National Research Council (NRC). A valuable resource for working professionals and involved parents, and the most current volume of information of its kind available on the market today --
Includes bibliographical references and index.
.
Keywords: Mathematics; Science; Education, Elementary; Education, Elementary; Mathematics; Science